Fracture mechanics of laser sintered cracked polyamide for a new method to induce cracks by additive manufacturing. (April 2016) - Brugo, T.; Palazzetti, R.; Ciric-Kostic, S.; Yan, X.T.; Minak, G.; Zucchelli, A.
Abstract: This paper presents an experimental investigation on specimens manufactured by Selective Laser Sintering (SLS), with the purposes of giving designers advice when designing 3D printed parts, and laying the basis for a step forward in the field of fracture mechanics of 3D complex parts. The aim is to investigate the effect of building direction in Polyamide (PA) 3D printed samples and to assess whether a crack can be initiated directly from the sintering process for fracture mechanics study purposes. Six different configurations of Mode I Compact Tension (CT) specimens were manufactured and tested; the experiments were monitored by Digital Image Correlation (DIC) and fractured surfaces were analyzed using microscopy. Results showed that samples with better mechanical performance are those in which all the layers contain a portion of the crack. On the other hand, those with layers parallel to the crack plan offer a preferential pathway for the crack to propagate. DIC and fractography investigations showed that, under certain conditions, small-radius geometries, or too-close surfaces may bond together depending on printer resolution. Experiments also showed that SLS is capable of printing specimens with internal cracks that can be used to study fracture mechanics of complex parts or parts with internal cracks.